2012
DOI: 10.1186/1475-2875-11-412
|View full text |Cite
|
Sign up to set email alerts
|

Local population structure of Plasmodium: impact on malaria control and elimination

Abstract: BackgroundRegardless of the growing interest in detecting population structures in malarial parasites, there have been limited discussions on how to use this concept in control programmes. In such context, the effects of the parasite population structures will depend on interventions’ spatial or temporal scales. This investigation explores the problem of identifying genetic markers, in this case microsatellites, to unveil Plasmodium genetic structures that could affect decisions in the context of elimination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
154
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(170 citation statements)
references
References 45 publications
8
154
1
7
Order By: Relevance
“…In confirmation of Anderson et al's (2000) observations, persistent MLGs were observed in P. falciparum for as long as 8 years (Nkhoma et al, 2013). Many authors have come to use the very terms "clones" and "clonal population structure" for describing the population structure of Plasmodium (Annan et al, 2007;Chenet et al, 2012;Ferreira et al, 2007;Griffing et al, 2011;Heitman, 2006;Karunaweera et al, 2008;Nkhoma et al, 2013;Razakandrainibe et al, 2005), which would have been unthinkable 20 years ago. In some populations, restrained recombination manifests itself, not only by LD and ubiquitous MLGs but also by a tendency of natural populations to be structured into lasting, stable clusters, which cannot be accounted for by isolation by distance and time.…”
Section: Population Structure Of Plasmodium Andmentioning
confidence: 55%
See 3 more Smart Citations
“…In confirmation of Anderson et al's (2000) observations, persistent MLGs were observed in P. falciparum for as long as 8 years (Nkhoma et al, 2013). Many authors have come to use the very terms "clones" and "clonal population structure" for describing the population structure of Plasmodium (Annan et al, 2007;Chenet et al, 2012;Ferreira et al, 2007;Griffing et al, 2011;Heitman, 2006;Karunaweera et al, 2008;Nkhoma et al, 2013;Razakandrainibe et al, 2005), which would have been unthinkable 20 years ago. In some populations, restrained recombination manifests itself, not only by LD and ubiquitous MLGs but also by a tendency of natural populations to be structured into lasting, stable clusters, which cannot be accounted for by isolation by distance and time.…”
Section: Population Structure Of Plasmodium Andmentioning
confidence: 55%
“…We will call it here the "starving sex hypothesis". It has been accepted by many authors in order to account for the observed population structure of Plasmodium (Arnott et al, 2012;Branch et al, 2011;Chenet et al, 2012;Conway, 2007;Ferreira et al, 2007;Gupta et al, 2012;Imwong et al, 2006Imwong et al, , 2007Iwagami et al, 2009;Mobegi et al, 2012;Mu et al, 2005;Mzilahowa et al, 2007;Neafsey, 2013;Neafsey et al, 2008;Nkhoma et al, 2013;Schultz et al, 2010;Volkman et al, 2012a,b). It can be challenged, as we will further see, since many observations are at odds with it, both in P. falciparum and in Plasmodium vivax.…”
Section: Population Structure Of Plasmodium Andmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 Moreover, since the P. falciparum population underwent strong drug selection, expansions of few drug-resistant parasite lineages is expected. 10 Epidemiological data suggest that the Cusco P. falciparum outbreak was the result of human migration from Loreto Department when a road construction company set up a camp in Rosalina to build a road to Kiteni, Echarate District. 2 In September 2013, prior to the outbreak, two road workers who were originally from Iquitos were diagnosed with severe malaria and, because of their critical condition, were subsequently transferred to another city for medical examination.…”
mentioning
confidence: 99%